2017
DOI: 10.1002/2017jb014280
|View full text |Cite
|
Sign up to set email alerts
|

Fabric heterogeneity in the Mojave lower crust and lithospheric mantle in Southern California

Abstract: We use xenoliths from young cinder cones in the eastern Mojave region of Southern California to investigate deformation fabrics and their implications for strain localization, lithospheric viscosity, and controls on mineral lattice‐preferred orientations (LPOs) and seismic anisotropy at Moho depths. Lower crustal gabbros and upper mantle peridotites were collected from two areas separated by ∼80 km—the Cima and Deadman Lake Volcanic Fields. At both localities, mantle peridotites exhibit solid‐state deformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 150 publications
(237 reference statements)
1
37
0
Order By: Relevance
“…Grain diameters—averaged for at least 100 grains per sample—were measured manually using this software. Results from this approach have been shown to agree with those of the linear intercept method, where grain size is estimated automatically from electron backscattered diffraction (EBSD) maps (Bernard & Behr, ). The experimentally derived empirical olivine paleopiezometer of Van der Wal et al () was used to estimate differential stress magnitudes from the average recrystallized grain sizes, after applying a correction factor of 1.2 to the average grain size to account for 2‐D sectioning (Drury, ; Van der Wal et al, ).…”
Section: Methodsmentioning
confidence: 74%
See 2 more Smart Citations
“…Grain diameters—averaged for at least 100 grains per sample—were measured manually using this software. Results from this approach have been shown to agree with those of the linear intercept method, where grain size is estimated automatically from electron backscattered diffraction (EBSD) maps (Bernard & Behr, ). The experimentally derived empirical olivine paleopiezometer of Van der Wal et al () was used to estimate differential stress magnitudes from the average recrystallized grain sizes, after applying a correction factor of 1.2 to the average grain size to account for 2‐D sectioning (Drury, ; Van der Wal et al, ).…”
Section: Methodsmentioning
confidence: 74%
“…Such efficient strain partitioning is supported by theory (e.g., Handy, ; Huet et al, ; Reuss, ) and consistent with observations from ophiolitic mantle lithosphere, where high degrees of strain are concentrated within narrow mylonitic shear zones (e.g., Homburg et al, ; Linckens et al, ; Skemer et al, ). Populations of xenoliths recovered from western U.S. localities suggest similar strain localization in subcontinental mantle (e.g., Behr & Hirth, ; Behr & Smith, ; Bernard & Behr, ; Wernicke et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For these samples, T used in plots is based on median value within this range. Exact sample T values for Elephant Butte and Cerro Chato samples come from Byerly and Lassiter (2012); Dish Hill and Cima samples from Bernard and Behr (2017). Regional T ranges from the following studies: San Carlos, Galer and O'Nions (1989);…”
Section: Sample Descriptionsmentioning
confidence: 99%
“…Measurements were averaged for at least 100 dynamically recrystallized grains or subgrains per sample. Prior work has demonstrated that this method yields virtually identical results compared to the linear intercept method conducted optically or using Electron Backscatter Diffraction (EBSD) data (Bernard & Behr, 2017). Average recrystallized grain sizes, after applying a correction factor of 1.2 to account for 2-D sectioning, were used to estimate deviatoric stress magnitudes during deformation based on the paleopiezometer of Van der Wal et al (1993).…”
Section: Grain Size Measurements and Stress Magnitudesmentioning
confidence: 99%